Entrepreneurship Development Opportunities For Women In The Kingdom Of Saudi Arabia - Khan, Anna; Zia, Tauseef Siddiqui (Universiti Sains Malaysia, 2016)

(untitled)
This paper is prepared with the aim to propose strategies and policies which could create an enabling environment for women entrepreneurs in the Kingdom of Saudi Arab. Off late women are taking the lead as game changers and reformers in the male dominated society. In the recently concluded municipal elections women candidates sprung a surprise by winning decent number of seats. Authors also aim to provide a set of practical recommendations to promote the healthy growth of entrepreneurial activities and enterprises owned by women. Empowering women has become the key element in the development of the Kingdom. With women moving forward, the family moves, the village moves and the nation moves. Hence, improving the status of women by way of their economic empowerment is highly called for.